Conformational and Functional Properties of Soybean Proteins Produced by Extrusion-Hydrolysis Approach - Wenjun Ma; Baokun Qi; Rokayya Sami; Lianzhou Jiang; Yang Li; Hui Wang (International Journal of Analytical Chemistry)
The conformational and functional changes of soybean protein after a hybrid extrusion-hydrolysis method were evaluated. Three extrusion temperatures (60, 80, and 100°C) were used prior to enzymatic hydrolysis. The hydrolysis degrees, molecular weight profiles, solubilities, surface hydrophobicities, sulphydryl contents, disulfide bound, water holding capacity, emulsion, and foam properties of the protein isolated from the enzyme-hydrolyzed extruded soybeans were analyzed. It shows that extrusion caused significant changes in the hydrophobicity, molecular weight distribution, solubility, surface hydrophobicity, emulsification activity, and stability of the protein. The increase of molecular weights could be attributed to the formation of protein aggregates during extrusion. Extrusion and enzymatic hydrolysis led to a sharp increase in the number of disulfide bonds with a decrease of the sulphydryl group. The water holding capacity and the solubility of protein increased with the increase of extrusion temperature and hydrolysis time. Extrusion improved the emulsifying activity but reduced the emulsifying stability of the recovered proteins. Extrusion improved the foam capacity but reduced the foam stability of the proteins. The data demonstrated that the extrusion-hydrolysis treatment significantly altered the conformational and functional properties of soybean protein, which may be further optimized for the development of new soy protein ingredient with desired functional properties.